HAK-HAK PEREMPUAN PASCA PERCERAIAN DALAM HUKUM POSITIF DAN HUKUM ISLAM - H. Hamzah; Oyo Sunaryo Mukhlas; Usep Saepullah (Usroh: Jurnal Hukum Keluarga Islam, 2022)
This article discusses women's rights after divorce in positive law and Islamic law. Women's rights after divorce are deemed necessary to be discussed further, because in the Indonesian legal system women's rights after divorce are guaranteed by the Supreme Court regulations, considering that marriage in Indonesian law is regulated based on positive law and Islamic law. The method used in this research is normative juridical with the type of literature study. The results of this study show that after the divorce, women's rights, especially a living are guaranteed in the Marriage Law, as well as the issuance of Perma number 3 of 2017. Then according to Islamic law, ex-husbands have an obligation to provide iddah and hadhanah to their wives and children, mut'ah maintenance for women who are divorced, as well as dowry debts that must be repaid immediately. Keywords: Women's Rights; Positive Law; Islamic Family Law